Attainment of Quiet Standing in Humans: Are the Lower Limb Joints Controlled Relative to a Misaligned Postural Reference? - Di Giulio, Irene; Baltzopoulos, Vasilios (Frontiers in Physiology, 2019)
In human quiet standing, the relative position between ankle joint centre and line of gravity is neurally regulated within tight limits. The regulation of the knee and hip configuration is unclear and thought to be controlled passively. However, perturbed standing experiments have shown a leg multi-joint coordination. Here, measuring the relative alignment between leg joints and the line of gravity in quiet standing after walking, we investigated whether the configuration is maintained over time through passive mechanisms or active control. Thirteen healthy adults walked without following a path and then stood quietly for 7.6s on a force platform (up to four trials). The transition between initiation and steady-state standing (7.6s) was measured using motion capture. Sagittal leg joint centres’ position relative to line of gravity (CoGAP) and their time constants were calculated in each trial. Ankle, knee and hip joint moments were also calculated through inverse dynamics. After walking, the body decelerated (τ=0.16s). The ankle and hip joints’ position relative to CoGAP measured at two time intervals of quiet standing (Mid=0.5-0.55s; End=7.55-7.6s) were different (mean±sem CoGAP-Ankle_Mid=47±4mm, CoGAP-Ankle_End=58±5mm; CoGAP-Hip_Mid=2±5mm, CoGAP-Hip_End=-5±5mm). The ankle, knee and hip flexion-extension moments significantly changed. Changes in joints position relative to CoGAP and misalignment suggest that joint position is not maintained over 7.6s, but regulated relative to a standing reference. Higher joint moments at steady-state standing suggest mechanisms other than passive knee and hip regulation are involved in standing.